The informal constitution : unwritten criteria in selecting judges for the Supreme Court of India - Chandrachud, Abhinav (New Delhi : Oxford University Press, 2014)
An empirical study of judicial appointments made to the Supreme Court of India since Independence. The historical debates surrounding the establishment of the Federal Court during the British Raj, debates in the Constituent Assembly of India and its sub-committees specific to the establishment of the Supreme Court, the three 'Judges Cases' and the political developments which led to the present 'collegium system' of appointing judges to the Supreme Court of India have all been discussed and analysed.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on May 27, 2014).
Keywords: Judges -- Selection and appointment -- India -- History -- 20th century; Judges -- Selection and appointment -- India -- History -- 21st century; India. -- Supreme Court -- Officials and employees